The relationship between salivary adrenocortical hormones changes and personality in elite female athletes during handball and volleyball competition - Filaire, E.; Le Scanff, C.; Duche, P.; Lac, G. (Research Quarterly for Exercise and Sport, 1999)
Salivary cortisol, androstenedione delta 4, and dehydroepiandrosterone (DHEA) in 20 elite sportswomen were measured using radioimmunoassay in samples taken 5 min before and after a handball or volleyball competition. Three psychometric tests--State Trait Anxiety Inventory, Bortner, and Questionnaire de Personnalite pour Sportifs (questionnaire of personality for sports participants)--were used to evaluate the participants' personalities. Results indicated higher concentrations of cortisol and lower concentrations of delta 4 and DHEA in handball players before and after the competition. Cortisol values increased significantly during the competition in both groups. No changes were observed in androgen levels. The state of anxiety was higher in handball players, characterized by Pattern A behavior, whereas Pattern B behavior defined the volleyball players. The results suggest that adrenocortical changes during handball and volleyball competition are influenced by the different energy systems required by the two activities, individual personality characteristics, and the athlete's anxiety level relative to winning or losing.